Peran Filsafat Pendidikan Islam dalam Pembentukan Karakter Peserta Didik di MTs N 2 Sukoharjo - Anshori, Nanang; Mujiburrohman, Mujiburrohman (Lembaga Yasin AlSys, 2025)
Character education is a fundamental aspect of the educational landscape, particularly within the context of Islamic education, which emphasizes moral and spiritual values. This study aims to examine the concept of Islamic educational philosophy in shaping students' character, explore its role at MTs N 2 Sukoharjo, and analyze the impact of its implementation on students' character development. A qualitative method with a descriptive approach was employed. Data were collected through direct interviews with teachers at MTs N 2 Sukoharjo and documentation from relevant literature, including books, journals, and scholarly articles. The findings reveal that Islamic educational philosophy plays a strategic role in character formation through madrasah programs integrated with values of tauhid, ethics (akhlak), and social responsibility. An educational environment grounded in these values fosters a madrasah culture that holistically supports character development. The study affirms that the application of Islamic educational philosophical principles makes a tangible contribution to student character development and offers practical implications for educational institutions in constructing a value-based educational system.